Comparison of the microstructure of machined and laser sintered shaped charge liner in the hydrodynamic regime - Agu, Henry; Hameed, Amer; Appleby-Thomas, Gareth J. (Springer, 2019)
To gain further insight into the mechanisms underlying jet formation and elongation of laser sintered shaped charge liners under high strain rate deformation, Cu–Cr–Zr alloy liners fabricated by selective laser sintering process were deformed by explosive detonation. Their as-manufactured (liner) and resultant (slug) microstructure have been investigated in comparison with those of traditional machined liners employing both optical and scanning electron microscopy. The resultant slug microstructure of both machined and laser sintered liners revealed a smaller refined equiaxed grain size consistent with traditionally fabricated liners, characteristic of dynamic recrystallization. The disappearance of the (originally present) pores in the post-shot/recovered material microstructure was observed for laser-sintered liners. Comparison of the forward and rear region of the slug revealed variations in liner deformation, a result attributed to temperature variation across the slug. In contrast with the machined liner, a unique feature of precipitation, observed in the ending (slug) microstructure of the laser sintered liner is indicative of the associated extreme high strain and strain rate liner deformation which occurred during slug formation. The precipitates are likely compounds of Chromium and Zirconium which are constituents of the laser sintered copper alloy—the first time this observation is reported. This study provides a link between post charge evolution microstructure and liner manufacturing processes, potentially providing a new route to help optimise jet formation and effectiveness.
Keywords: Liner; Laser sintering process; Shaped charge; Copper; Microstructure; Temperature